Effect of sintering conditions on physical properties of carbonated hydroxyapatite ceramics - Tkachenko, M.V.; Zyman, Z.Z. (Functional Materials, 2008)
The carbonated hydroxyapatite powder was obtained by reaction of calcium carbonate with ortho-phosphoric acid. The compacted powder samples were sintered in the 800- 1000°C range in dry carbon dioxide atmosphere under atmospheric pressure. It is revealed that ceramics synthesized in such conditions is the AB type carbonated hydroxyapatite. The carbonization kind varies from mainly B type (at relatively low sintering temperatures) to mainly A type (at high ones). The carbonic gas atmosphere did not allow to suppress disintegration of a carbonated apatite at a sintering temperatures above 1100°C, a partial decomposition of the B type apatite occurs with calcium oxide release. As a result, porosity of the ceramics increases and its mechanical properties drop sharply. However, at temperatures below 1100°C, the carbon dioxide favors the activated shrinkage of compacts due to accelerated diffusion migration of the powder particles. In particular, the maximum density of ceramics (~94% from the theoretical value) is reached at 1000°C. Порошок карбонізованого гідроксилапатиту отримано реакцією між карбонатом кальцію та ортофосфорною кислотою. Виготовлені з нього пресовані зразки спікалися в інтервалі температур 800-1000°С у атмосфері сухого діоксиду вуглецю (при нормальному тиску). Кераміка, отримана у такий спосіб, є карбонізованим гідроксилапатитом АЕ-типу. Вид карбонізації змінюється від переважно В-типу при відносно низьких температурах до переважно А-типу - при високих температурах спікання. Вище 1100°С відбувається частковий розпад апатиту В-типу та виділення окису кальцію. При цьому пористість кераміки зростає та різко падають її механічні властивості. При температурах нижче 1100°С атмосфера діоксиду вуглецю сприяє активованій усадці пресовок завдяки прискоренню дифузійної міграції частинок порошку. Зокрема, це приводить до досягнення високої щільності кераміки (~94% від теоретичного значення ГА) при температурі 1000°С. Порошок карбонизированного гидроксилапатита получен путем проведения реакции между карбонатом кальция и ортофосфорной кислотой. Изготовленные из него прессовки спекались в интервале температур 800-1000°С в атмосфере сухого углекислого газа (при нормальном давлении). Керамика, полученная таким способом, является карбонизированным гидроксилапатитом АВ-типа. Вид карбонизации изменяется от преимущественно В-типа при относительно низких температурах до преимущественно А-типа - при высоких температурах спекания. Выше 1100°С происходит частичный распад апатита В-типа и выделение окиси кальция. При этом пористость керамики увеличивается и резко падают ее механические свойства. При температурах нижe 1100°С, атмосфера углекислого газа способствует активированной усадке прессовок благодаря ускорению диффузионной миграции частиц порошка. В частности, это приводит к достижению высокой плотности керамики (~94% от теоретического значения ГА) при температуре 1000°С.